Tinjauan Biblikal Terhadap Tujuan Ucapan Kutuk Elisa Dalam 2 Raja-Raja 2:23-25 - Yaaro Harefa; Yolin Ilo (Philoxenia: Jurnal Teologi dan Pendidikan Kristiani, 2023)
Elisha's act of cursing the children in 2 Kings 2:23-25 raises many perceptions and even makes it difficult for readers to understand texts like this. How could a man of God utter such a curse word? Therefore, the researcher investigated this topic using a qualitative method with an exegetical approach. The researcher found that this text is not problematic if the reader can understand the purpose behind Elisha's words. Prophecy is entirely God's decision and action for the benefit of His people. This is a special task that God has given him to do on this earth. Accepting and honoring God's messengers is a form of acceptance of God through the Word that is delivered. The truth they preach is the truth of God's grace for man to attain salvation in Christ. Humans are given two choices, namely accepting the truth of God's Word or turning away from God, because God has given free will for humans to choose. The punishment given to those who reject God is the eternal punishment to come.